DAMPAK SERTA UPAYA PENANGANAN IMPOR PASCA ACFTA DI PROPINSI JAWA TENGAH - Reni K Arianti; Adrian D Lubis (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
The implementation of the ACFTA liberalization is consider as the root of the problem on the regional trade performance, including Central Java. This study used regression analysis with dummy variables. The results show that increasing imports and deficit trade balance has occurred long before the ACFTA liberalization. The main causes of these deficits are the high dependence on high value-added consumer products from China and the failure to increase exports of high value-added products to China.Keywords:  ACFTA, Central Java, Regression Analysis